2014
DOI: 10.1111/jfb.12425
|View full text |Cite
|
Sign up to set email alerts
|

Diet composition and feeding ecology of the naked goby Gobiosoma bosc (Gobiidae) from four western Atlantic estuaries

Abstract: The feeding ecology of the small-bodied benthic naked goby Gobiosoma bosc, a western Atlantic species that occurs in estuaries and other inshore habitats from Connecticut to Texas U.S.A., was investigated in a total of four estuaries spanning South Carolina, North Carolina, Maryland and New Jersey. Gut content analysis of 391 individuals revealed that G. bosc is a benthic microcarnivore that feeds primarily on polychaetes, gammarid amphipods and harpacticoid copepods. Diet composition varied with body size, ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 57 publications
0
8
0
Order By: Relevance
“…(2010b) also observed this in their results, since even the largest individuals of A. brasiliensis presented as main food item Calanoida. Other studies have shown a linear relationship between the size of the mouth and the size of the prey consumed (D'Aguillo et al ., 2014; Mendoza‐Carranza & Vieira, 2009; Mogensen & Post, 2012). These characteristics of feeding among the size classes only reinforce that the A. brasiliensis species presents a generalist‐opportunistic habit, feeding on what is abundant in the estuary.…”
Section: Discussionmentioning
confidence: 99%
“…(2010b) also observed this in their results, since even the largest individuals of A. brasiliensis presented as main food item Calanoida. Other studies have shown a linear relationship between the size of the mouth and the size of the prey consumed (D'Aguillo et al ., 2014; Mendoza‐Carranza & Vieira, 2009; Mogensen & Post, 2012). These characteristics of feeding among the size classes only reinforce that the A. brasiliensis species presents a generalist‐opportunistic habit, feeding on what is abundant in the estuary.…”
Section: Discussionmentioning
confidence: 99%
“…We stand to learn a great deal from studying common fish like G. bosc that, notwithstanding their abundance, remain relatively understudied in the literature. Only recently, for example, was a comprehensive analysis published on the feeding ecology of this species (e.g., D’Aguillo, Harold & Darden, 2014 ), which addressed basic questions like diet and daily patterns in foraging activity. In the future, we intend to continue to address the limited understanding of the basic biology of this species by resolving questions of adult dispersal—in particular by studying the movement patterns of adult G. bosc that reside in specific habitat patches.…”
Section: Discussionmentioning
confidence: 99%
“…Although G. bosc and other organisms can freely move inside and outside the crates, they are attracted to the complex three-dimensional habitat that the shell provides. This is analogous to the collecting strategy used by D’Aguillo, Harold & Darden (2014) , who employed habitat traps (i.e., “shell-rubble trays”: 0.8 m 2 plastic trays covered with 0.6 cm mesh netting and filled with oyster shell) to sample specifically for naked gobies.…”
Section: Methodsmentioning
confidence: 99%
“…In addition to abundance, invertebrate diversity is important. Predators exploit a variety of invertebrates (e.g., D'Aguillo et al, 2014, Selleslagh et al, 2015, which may provide a stable prey base despite variation in individual species abundances across time and space (sensu Schindler et al, 2015). Thus, functional nearshore habitats enable abundant, diverse invertebrate assemblages that support nutrient and energy flow across habitat types and consumers.…”
Section: Introductionmentioning
confidence: 99%